Halitosis and pain threshold of peri-implant tissues: An observational cohort study - Do Vale Souza, João Paulo [UNESP]; Romero, Giovana Domelas Azevedo [UNESP]; De Moraes Meló Neto, Clóvis Lamartine [UNESP]; Piaeenza, Lucas Tavares [UNESP]; Monteiro, Renata Vasconcelos; Da Silva, Emily Vivianne Freitas; Dos Santos, Daniela Micheline [UNESP]; Goiato, Marcelo Coelho [UNESP] (FapUNIFESP (SciELO), 2023)
In this study, we aimed to evaluate the halitosis and pain threshold of the peri-implant soft tissues in individuals rehabilitated with implant-supported prostheses. Forty-eight subjects were divided into four groups (n = 12) according to their prosthetic rehabilitation: Single-tooth fixed prosthesis, multi-tooth fixed prosthesis, overdentures, and the Branemark protocol. Halitosis was measured using a halimeter, whereas the pain threshold was measured using Von Frey monofilaments. Measurements were taken before (to) and 30 days after (t1) placement of healing caps, and at the time of (t2) and 30 days after (t3) prosthetic placement. Halitosis data were analyzed using the chi-square test and Bonferroni correction (p < 0.05). Two-way ANOVA and Tukey's test (p < 0.05) were used to analyze pain threshold data. We noted an association between halitosis and time for the Brånemark protocol [X2(6) = 18.471; ρ = 0.005] and overdenture groups [X2(6) = 17.732; ρ = 0.007], and between halitosis and type of prosthesis only at tO [X2(6) = 12.894; ρ = 0.045]. The interaction between time and the type of prosthesis significantly interfered with the mean pain threshold values (p = 0.001). At most time points, the majority of participants in each group had clinically unacceptable halitosis. After 30 days of using the prostheses, the overdenture group had a lower pain threshold compared to the Branemark protocol group.
Keywords: Edentulous mouths; Halitosis; Implant-supported dental prosthesis